Development of Instrument Assessment of Pancasila Student Profile Assisted by Google Form on Material Quadrangle in Grade IV SD Negeri 104607 Sei Rotan - Nur Habibah; Dian Armanto; Kms. M. Amin Fauzi (Randwick International of Education and Linguistics Science Journal, 2023)
Instruments in learning have an important role in obtaining information about achieving student competencies objectively. This study aims to describe the validity of the Pancasila student profile instrument developed. This research is development research conducted using the preparation of test and non-test instruments by Mardapi. The subjects in this study were grade IV students of SD Negeri 104607 Sei Rattan totaling 44 students. From the results of the trial obtained: 1) the validity of the developed instrument is valid in terms of the results of advance validation and content validation. As well as the results of trials with students are declared valid and have high reliability.